Maternal Exposure to Air Pollution and Adverse Birth Outcomes in Halifax, Nova Scotia. Issue 12 (December 2015) - Poirier, Abbey; Dodds, Linda; Dummer, Trevor; Rainham, Daniel; Maguire, Bryan; Johnson, Markey
Abstract : Objective: We aimed to examine the associations between exposure to air pollution exposure and the outcomes of preterm birth (PTB), term low birth weight (TLBW), and small for gestational age. Methods: We conducted a population-based cohort study using a perinatal database linked to land-use regression-modeled air pollution data. Results: Compared with women in the lowest quartile of toluene exposure, those in the second lowest quartile showed a positive association with PTB (odds ratio = 1.35, 95% confidence interval: 1.12, 1.63). A piecewise logistic regression breakpoint analysis identified a cut point (identifying a change in the slope) of 0.36 μg/m 3 for toluene and the risk of PTB. There was also some evidence to suggest an association between sulfur dioxide and TLBW. Conclusions: This study provides some evidence to suggest that in an area of relatively low air pollution concentration, maternal exposure to some air pollutants may be associated with adverse birth outcomes.